2021
DOI: 10.1111/jocd.14534
|View full text |Cite
|
Sign up to set email alerts
|

Acne scar treatment using high‐energy fractional nanosecond Q‐switched 1064 nm laser

Abstract: Acne vulgaris is one of the most common skin diseases; it will affect one out of two people in their lifetimes and about 80% of people aged between 11 and 30 years. [1][2][3] Acne scarring, a common complication, develops to some degree in the majority of acne sufferers. 4 Scars are divided into three general categories: ice-pick scars, rolling scars, and boxcar scars 5 and are a result of excessive inflammation, acne severity, physical manipulation of the skin, and a delay in seeking adequate treatment. 3 It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a study published in the Journal of Cosmetic and Laser Therapy, researchers assessed patient satisfaction after fractional laser therapy for acne scars. The research found a high satisfaction rate of 80%, with patients reporting better scar appearance, greater selfesteem, and overall happiness with the treatment results [22].…”
Section: Patient Satisfaction Ratesmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study published in the Journal of Cosmetic and Laser Therapy, researchers assessed patient satisfaction after fractional laser therapy for acne scars. The research found a high satisfaction rate of 80%, with patients reporting better scar appearance, greater selfesteem, and overall happiness with the treatment results [22].…”
Section: Patient Satisfaction Ratesmentioning
confidence: 92%
“…After getting the surgery, several patients report enhanced self-esteem and life quality. With fractional laser therapy, patient-reported outcomes and surveys regularly reveal high levels of satisfaction and pleasant experiences [22]. In a study published in the Journal of Cosmetic and Laser Therapy, researchers assessed patient satisfaction after fractional laser therapy for acne scars.…”
Section: Patient Satisfaction Ratesmentioning
confidence: 99%
“…18 In-office procedures may include chemical peels, microdermabrasion, microneedling, and energy-based methods such as laser treatments for melanin removal. [19][20][21] DiamondGlow® (DG; Allergan Aesthetics, an AbbVie Company, Irvine, CA, USA) is a noninvasive, in-office procedure using a pro- (HQ)-free, pigment-correcting topical skincare products that target multiple cellular pathways in melanogenesis to treat broadly dispersed hyperpigmentation and dark spots (such as PIH and solar lentigines), respectively. 22,23 The objective of this study was to assess cosmetic changes in subjects with mild to severe overall facial hyperpigmentation who received a combination of a series of 6 DG procedures using EC-DG, along with an at-home skincare regimen comprising ABT and spot cream.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, combination treatments that involve an in‐office procedure, along with an at‐home topical regimen, have demonstrated greater efficacy than single treatments alone, and help to reduce risk of recurrence of hyperpigmentation 18 . In‐office procedures may include chemical peels, microdermabrasion, microneedling, and energy‐based methods such as laser treatments for melanin removal 19–21 …”
Section: Introductionmentioning
confidence: 99%